Political decision-making and the decline of Canadian peacekeeping. Issue 2 (4th May 2019) - Young, Graeme
ABSTRACT: This article explores the reasons behind Canada's declining participation in United Nations peacekeeping operations. It proposes a decision-making model that explains how politicians assess opportunities to commit personnel to peacekeeping missions by balancing their policy objectives with the pressures of electoral politics. Emphasizing the importance of voters in political decision-making processes, it argues that participation in peacekeeping is dependent on three key factors: a belief in the value of peacekeeping in principle; a belief in the value of a given peacekeeping operation; and risk aversion in response to the potential costs of peacekeeping. Tracing Canada's declining participation in peacekeeping operations since the 1990s, it particularly focuses on how this calculus has, in different ways, limited Canada's involvement in peacekeeping under Stephen Harper's Conservative government and Justin Trudeau's Liberal government, arguing that the former undervalued peacekeeping as a means of obtaining its foreign policy objectives and as a feature of national identity, minimizing the perceived benefits of participation, while the latter has focused on the inherent risks of peacekeeping despite a professed commitment to peacekeeping in principle, maximizing the perceived costs of further personnel commitments. The decisions of successive Canadian governments have led to a free-rider problem in which Canada is willing to enjoy the benefits of peacekeeping but unwilling to bear the costs.